CerAMfacturing of silicon nitride by using lithography-based ceramic vat photopolymerization (CerAM VPP). Issue 2 (February 2023) - Schwarzer-Fischer, Eric; Zschippang, Eveline; Kunz, Willy; Koplin, Christof; Löw, Yannick Marian; Scheithauer, Uwe; Michaelis, Alexander
Abstract: Hardness, high mechanical strength, wear and corrosion resistance, for instance, are the most important properties of silicon nitride. Next to technical application, the material becomes more and more important for medical applications, especially for implants and the focus in research for this increase steadily. Up to now, the demands on the geometry of silicon nitride-based components could largely be met by using conventional shaping methods such as pressing and green machining or injection moulding. However, requirements in terms of complexity and function are constantly increasing. By using additive manufacturing (AM) technologies, the complexity of components can be significantly increased and additional functions such as transport channels or features like triple periodic minimal surfaces (TPMS), which seem to be advantageous for osseointegration can be integrated, for instances. High-resolution AM processes such as stereolithography enable the production of very accurate and complex ceramic components. In this work a silicon nitride suspension suitable for biomedical applications was developed and the influence of the formulation on the properties (especially flow and curing behavior) were analyzed. Afterwards, various test samples were generated by ceramic additive manufacturing via vat photopolymerization (CerAM VPP), thermally processed and the sintered parts were characterized with common ceramic methods, like mechanical tests and microstructure analyses, showing satisfying results for the described development state.